Chemoreception of Mouthparts: Sensilla Morphology and Discovery of Chemosensory Genes in Proboscis and Labial Palps of Adult Helicoverpa armigera (Lepidoptera: Noctuidae) - Guo, Mengbo; Chen, Qiuyan; Liu, Yang; Wang, Guirong; Han, Zhaojun (Frontiers in Physiology, 2018)
Siphoning mouthparts, which mainly consist of proboscis and labial palps, are the exclusive feeding organs and important chemosensory organs in most adult Lepidoptera. In this study, general morphology of the mouthpart organs and precision architecture of the proboscis was described in adult H. armigera. Three major sensilla types with nine sub-types including three novel sub-types were identified. The novel sensilla styloconica sub-type 2 was the only one owning multiporous structure, which may play olfactory roles. For further understanding of the chemosensory functions of mouthpart organs, we conducted transcriptome analysis on labial palps and proboscises. A total of 84 chemosensory genes belonging to six different families including 4 odorant receptors (ORs), 6 ionotropic receptors (IRs), 7 gustatory receptors (GRs), 39 odorant binding proteins (OBPs), 26 chemosensory proteins (CSPs), and 2 sensory neuron membrane proteins (SNMPs) were identified. Furthermore, 8 OBPs and 6 CSPs were identified as the novel genes. The expression level of candidate chemosensory genes in the proboscis and labial palps was evaluated by differentially expressed genes (DEGs) analysis and the expression of candidate chemosensory receptor genes in different tissues was further investigated by quantitative real time PCR (qRT-PCR). All the candidate receptors were detected by DEGs and qRT-PCR, but only a small part of the OR or IR genes specifically or bias expressed in proboscis or labial palps, such as HarmOR58 and HarmIR75p.1, But most of the GRs expressed abundantly in proboscis or labial palps. The reported CO2 receptors HarmGR1, GR2, GR3 mainly expressed in labial palps. HarmGR5, GR6, GR8, which belonging to “sugar receptor” clade, mainly expressed in proboscis or antenna and were therefore suggested to perceiving saccharide. The results suggest the mouthparts are mutually cooperative but functionally concentrated system. These works contribute to the understanding of chemical signal recognition in mouthpart organs and provides the foundation for further functional studies.